(untitled) (Nigerian Journal of Physiological Sciences, 2019)
Cephalometry of an ethnic population is determined by sex, diet, geographic location and genetics. Quantitative facial morphometry is necessary in today’s contemporary society because of the globalization of crime and justice. The objective of this study is to determine Yoruba ethnic population’s cephalofacial uniqueness for gender identification. A total of 222 adults (155 females and 67 males) participants from 10 local government areas in 5 states of the South-west Nigeria were randomly selected. Pre-defined set of cephalometric parameters were measured using standard requirement for anthropometry. Statistical analysis was calculated for gender differences using SPSS 20. Overall, gender differences (male vs female) was exhibited in head length, head width, upper facial height, lower facial height and facial width. Sexual differences were also exhibited in head modulus index (41.43±1.72 cm Vs 42.87±2.18 cm) and the index of the size of head (2361.89±444.53 cm3 vs 2147.78±316.13 cm3). Both genders exhibited dolichocephalic/mesocephalic type. Gender identification in this ethnic group may concentrate on five facial morphometry.